Keeping children at school - factors affecting attendance and children's academic achievement - Department of Social Services (Department of Social Services, 2015)
This article uses 5 waves of data from the Longitudinal Study of Indigenous Children to examine factors affecting attendance and academic achievement of Indigenous children.
Footprints in Time: The Longitudinal Study of Indigenous Children: Report from Wave 5
Keywords: Children -- Indigenous; Education and Training -- Primary; Learning, education and training; Children; Education and Training; Indigenous; Primary; Learning, education and training